2021
DOI: 10.1097/md.0000000000025643
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in incidence and outcomes of out of hospital cardiac arrest

Abstract: Out of hospital cardiac arrest (OHCA) remains a leading cause of mortality among adults in the United States. Environmental impact on incidence and outcomes of OHCA has not been fully investigated in recent years. Previous studies showed a possible increase in incidence and mortality in winter season and during seasons with temperature extremes. This study examines seasonal variation in incidence and outcomes of OHCA in the United States. Retrospective study of adult OHCA using the Nationwide Emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
(69 reference statements)
0
6
0
Order By: Relevance
“… 20 Likewise, the higher occurrence of cardiac arrest during Q2-Q4 may be due to increased vasoconstriction, higher blood pressure, blood viscosity, and fibrinogen levels. 21 , 22 Given these findings and previous research suggesting higher rates of complications during winter months, 23 future research may be warranted to investigate clinical outcomes in lung transplant recipients during the winter months. 24 , 25 Nevertheless, it should be duly noted that although dehiscence, pulmonary embolism, and cardiac arrest were statistically significantly more prevalent in Q2-Q4 versus Q1, the prevalence of each of these complications from a clinical standpoint may be less important.…”
Section: Discussionmentioning
confidence: 90%
“… 20 Likewise, the higher occurrence of cardiac arrest during Q2-Q4 may be due to increased vasoconstriction, higher blood pressure, blood viscosity, and fibrinogen levels. 21 , 22 Given these findings and previous research suggesting higher rates of complications during winter months, 23 future research may be warranted to investigate clinical outcomes in lung transplant recipients during the winter months. 24 , 25 Nevertheless, it should be duly noted that although dehiscence, pulmonary embolism, and cardiac arrest were statistically significantly more prevalent in Q2-Q4 versus Q1, the prevalence of each of these complications from a clinical standpoint may be less important.…”
Section: Discussionmentioning
confidence: 90%
“…One of the main causes of postoperative complications are aggravations of coexisting cardiac or respiratory comorbidities and cyclical variations have been shown in the incidence of cardiopulmonary pathologies, mainly during the winter months. Likewise, a cyclical pattern has been suggested for shortterm outcomes of surgery [24][25][26]. It has been reported that postoperative complications in pancreatic or bariatric surgery may present variable incidence, with peak periods of worse outcomes that could show a monthly cyclical pattern [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the clinical outcomes of patients with OHCA occurring during the cold season are worse than those in the hot season [ 3 , 4 , 5 ]. Specific diseases (e.g., myocardial infarction, respiratory diseases, and ischemic heart diseases) [ 6 ] that often occur and are complicated by cold conditions may explain the lower survival rates of patients with OHCA in the cold season.…”
Section: Introductionmentioning
confidence: 99%